THE IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT COMPONENT ON GUEST LOYALTY TOWARD STARRED HOTEL IN YOGYAKARTA - Dasril Indra; Ersy Ervina (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2020)
Purpose: This study aims to identify the overview of customer relationship management, analyze the level of hotel guest loyalty, and analyze the effect of customer relationship management consisting of services for the long term, individual service programs and partner relationships to the loyalty of hotel residents both simultaneously and partially. Research methods: This research was conducted in a descriptive and verification manner, while the research method used was a descriptive survey and explanatory survey methods, using samples through probability sampling techniques. Data collection used was interviews using a questionnaire accompanied by observation techniques. Data collection in the field was carried out in 2019. Data analysis used Path Analysis. Results and discussions: The results of this study indicate that; indicators of customer relationship management, and customer loyalty in four-star hotels in Yogyakarta City are generally rated well by customers, which means that four-star hotels in the City of Yogyakarta can raise good customer relationships and can provide high value and loyalty to their customer. Conclusion: Customer relationship management both simultaneously and partially affects the loyalty of four-star hotel customers in the city of Yogyakarta.